1973
DOI: 10.1002/j.2050-0416.1973.tb03525.x
|View full text |Cite
|
Sign up to set email alerts
|

The Suppression of Gushing by the Use of Hop Oil

Abstract: The addition to beer of small amounts of hop oil provides a means of suppress ing gushing, without adversely affecting foam stability. The hydrocarbon fraction of hop,oil is a more effective gushing suppressor than the oxygenated fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…In the case of hop oils (linalool and HOTD) as well as with Rho 35% (potassium salts of reduced iso-α-acids) and Tetra 10% (potassium salts of tetrahydro-iso-α-acids), addition led to a reduction of gushing volumes with the highest reduction achieved by the addition of hop oils. This is in accordance with results published previously 12,25 . The findings are also supported by the very recent work of Hanke et al 17 The effects observed could be caused by the foam negative properties of the oil.…”
Section: Discussionsupporting
confidence: 94%
“…In the case of hop oils (linalool and HOTD) as well as with Rho 35% (potassium salts of reduced iso-α-acids) and Tetra 10% (potassium salts of tetrahydro-iso-α-acids), addition led to a reduction of gushing volumes with the highest reduction achieved by the addition of hop oils. This is in accordance with results published previously 12,25 . The findings are also supported by the very recent work of Hanke et al 17 The effects observed could be caused by the foam negative properties of the oil.…”
Section: Discussionsupporting
confidence: 94%
“…A summarized extract of the scientific articles by Hanke et al [37][38][39] is presented in the following section. The gushing reducing effect of hop components such as linalool, hop oil and humulones, already known from former research 8,25,26,62,73,78 , was confirmed by their latest experiments 38,39 . The results supported observations in the brewing industry that beer with a higher hop addition (e.g., pilsner beer) shows lower gushing propensity than beer with a lower amount of hop addition.…”
Section: Introductionmentioning
confidence: 67%
“…Diverse experiments have shown that the volatile hop compounds (i.e., the hop oils), in particular ones that are not evaporated in such a set-up, can diminish the amount of gushing. More detailed information about the anti-gushing effects of hop oils can be found in the literature 1,6,10,11,15,20,21 . Many researchers have focussed on the relationship between fatty acids and the overfoaming volume 1,2,9,11,14,18,24 .…”
Section: The Influence Of the Hop Variety On The Overfoaming Volumementioning
confidence: 99%
“…Hops in particular contribute to a wide range of both aspects, depending on the sole point of usage or type of product. Inhibitory effects are shown by α-acids 13,14,20,21 and the unsaturated fatty acids that are included in hop oils 2,11,14 . A late hop addition that favours the transfer of linalool into the wort can also suppress the gushing volume 14 .…”
Section: Introductionmentioning
confidence: 99%